Does Islamic Banking Foster Sustainable Economic Development? Critical Perspectives on Growth, Financial Inclusion, and Stability - Kusnan; Sri Ermeila; Rahmi Aryanti; Junaidi Junaidi (Yayasan Darussalam Patalassang, 2026)
The Islamic banking sector has demonstrated substantial expansion since its inception; however, its global market share remains disproportionately low, particularly within Muslim-majority nations facing declining GDP growth. This study aims to evaluate whether Islamic banking genuinely fosters sustainable economic development by analyzing its specific influence on four dimensions: economic growth, profitability, financial stability, and distributive justice. Employing a systematic qualitative meta-synthesis and analytical review framework, this research triangulates empirical findings across these macroeconomic dimensions, focusing on Organization of Islamic Cooperation (OIC) member states. The findings indicate a mixed impact on sustainable development. First, regarding economic growth, Islamic banking's current scale and heavy reliance on non-PLS contracts severely limit its macroeconomic influence on national GDP. Second, profitability is positively correlated with macroeconomic factors, though it remains constrained by operational mimicry of conventional counterparts. Third, concerning financial stability, smaller-scale Islamic banks demonstrate stronger resilience and stability compared to larger commercial entities. Finally, in terms of distributive justice, Islamic banks successfully act as catalysts for financial inclusion and social finance, though true equitable wealth distribution remains suboptimal. The novelty of this research lies in its analytical triangulation of micro-financial viability against macroeconomic intermediation, providing a multidimensional assessment of how operational deviations hinder systemic sustainability. To achieve genuine economic sustainability, the Islamic banking sector must reform its operational models by prioritizing real-sector PLS financing, enhancing support for small and medium-sized enterprises (SMEs), and fostering comprehensive stakeholder collaboration.